Vài nhận xét về việc ứng dụng lý thuyết quá trình dừng để xử lí các tín hiệu số - Cầu, Phan Đăng (Journal of Computer Science and Cybernetics, 2016)
In this paper, by giving two examples, we would like to show that in some cases, it is reasonable to consider the sample correlation as a notion independent of the correlation function. We introduce  the notion of a long-run stationary process and some properties.